Remittance and Inflation Nexus in Bangladesh: Application of Dynamic ARDL Model with Linear Trend - Syed Margub Elahi; Md. Hasanur Rahman (Indonesian Journal Of Business And Economics, 2021)
Remittance is one of the major sources of financial inclusion in Bangladesh. The contribution of remittance to the economy gradually increases with respect to time. The current study investigates the nexus between remittance and inflation by considering data from 1975 to 2019. The results of the Augmented Dickey Fuller (ADF) unit root indicate the variables are stationary at mixed order like as I(0) and I(1). Through the ADF test, this study conducts a dynamic autoregressive distributed lag (ARDL) model with considering the linear trend. The remittance has a significant and positive impact to raise inflation in the short run but is insignificant in the long run. The estimation found the speed of adjustment, Error correction term (ECT) is 69% and bound testing criteria indicate the long-run association among the variable. This investigation also concludes that the exchange rate has a positive impact on inflation where the real exchange rate has no positive impact to raise inflation in Bangladesh. The empirical findings suggest the productive and safe investment rathe expense in consumption purpose due to reducing the consequence of remittance inflows on inflation in Bangladesh.